Prinsip Jaminan Hukum Sebagai Jaminan Sertifikasi Tanda Tangan Elektronik - Rizqi Robi Ali Sodiqin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Technological developments by international organizations see the need for recognition and regulation of legal certainty in the field of information technology, regarding electronic transactions with digital signatures. Legal certainty regulates clearly and logically, which means there is clarity and firmness in the application of law to e-signature regulations, and e-signature certification to guarantee legal certainty. Regulations on the use of e-signatures are regulated in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. Recognition of electronic signatures as valid legal evidence and electronic certification providers. The use of e-Signature is also regulated in implementing laws and regulations, namely Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, including the introduction of electronic signatures as a legal instrument, electronic signatures as a means of authentication and verification, data for creating electronic signatures , electronic signature signing process, electronic certification organizer. To use electronic signatures, you need to choose a company that has received certification and can operate globally without having to worry about document security.